Model Implementasi Kebijakan Pengembangan Taman Bacaan Masyarakat (TBM) di Kabupaten Purwakarta - Hamdan Yuafi; Deddy Mulyadi; Teni Listiani (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
The purpose of this study was to determine the implementation of policies for the development of public reading gardens in Purwakarta Regency and to identify the driving and inhibiting factors in the implementation of the community reading garden development policy. In addition, this research will also formulate a model for implementing policies for the development of reading gardens. The method used is descriptive qualitative research methods. The sample in this study is located in Purwakarta Regency. The results of this study indicate that the implementation of the TBM development policy in Purwakarta Regency has not been effective, the community has not made reading parks as a vehicle for education because of the lack of reading material collections that do not meet the information needs of the community. In addition, seen from the resource factor, the quality of human resources is not adequate. This is supported by budget constraints. The interest in primary needs makes people less concerned about literacy culture. So that in order to create regulatory harmonization with partners carried out by the Office of Archives and Libraries (Disipusda) of Purwakarta Regency, it is necessary to integrate policies for the implementation of non-formal education services through the formulation of new Regional Regulations (updating) which cover resource management including the division of roles between stakeholders.